PELATIHAN PEMBUATAN MEDIA KOMIK UNTUK MENINGKATKAN LITERASI DAN KEMAMPUAN PEMECAHAN MASALAH SISWA - Hayati, Rahmi; Yessi Kartika; Zuraini, Zuraini; Husnidar; Meilinar, Fina; Jannah, Niatul; Rusyidah (RAMBIDEUN : Jurnal Pengabdian Kepada Masyarakat, 2024)
Training on the use of comic media to improve literacy and students' problem-solving skills was held at the UPTD SMP Negeri 4 Peusangan on September 3-4, 2024, with the aim of helping teachers create more innovative, interesting, and effective learning. This activity involved teachers from various subjects with a theory-based approach, direct practice, and learning simulations using comic media. This training provides assistance to teachers in integrating comics into the classroom learning process, as well as conducting comic-based learning simulations by involving students as part of the media testing process. The results of the training showed an increase in teacher competence in designing and producing learning comics that are relevant to the curriculum. A total of 15 teachers successfully completed their comics and implemented this media in learning simulations. Obstacles faced during the training included limited technological facilities, variations in teacher abilities, and limited time. However, these can be overcome with intensive assistance, the use of simple applications, and collaboration between participants. The outputs of the activity were in the form of learning comics, training modules, and the formation of teacher discussion groups as a sustainable effort. Thus, students' learning motivation, literacy skills, and problem solving through the visual and narrative approaches presented in comics increased. This training has a significant positive impact, both for teachers, students and schools, and has become a development for subsequent learning innovations.